Sexagem molecular em aves: contribuições à conservação biológica e á divulgação científica - Gonçalves, Bianca Picado [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Birds represent a large part of the animals associated to illegal trade and commerce in Brazil, mainly due to some characteristics as song and feathers colors. Nowadays, genetic analyses comprehend one of the most efficient approaches to generate data in order to solve and minimize the results of environmental crimes and illegal trade of wild animals. Therefore, this work intent to perform sex identification genetic analyses in several birds, including species that are commonly associated to illegal animal trade and apprehended by the Environmental Policy and by IBAMA (Brazilian Institute of Environment and Renewable Natural Resources), and generate a scientific broadcasting material about illegal trade and conservation of this vertebrate group. DNA samples were obtained from feathers and blood of 124 individuals that belong to 53 species of the families Accipitridae, Cacatuidae, Cardinalidae, Cariamidae, Columbidae, Cuculidae, Emberezidae, Falconidae, Icteridae, Musophagidae, Psittacidae, Ramphastidae, Sturnidae, Thraupidae, Tinamidae, Trochilidae, and Turdidae, maintained by a Wildlife Reception, Screening and Rehabilitation Center (Floravida Institute NGO), a Wildlife Animal Health and Research Center (Faculty of Veterinary Medicine and Zootechny, São Paulo State University Botucatu, SP) and to two scientific breeding grounds of wild fauna based on conservation purposes (Criadouro C.A., Itatiba, SP and Criadouro Poços de Caldas, Poços de Caldas, MG). Sex-specific genetic profiles were generated by the amplification of DNA segments of the Z and W chromosomes. A primer set that anneal to exon regions of the CHD-Z and CHD-W (chromo helicase-DNA binding) genes and that amplify an intron region that differ in size between the two genes was used in PCR (Polymerase Chain Reaction) and the amplification products were visualized in 2% agarose gel. Two different size DNA fragments were evidenced for females and a single fragment was ...

Entre os animais silvestres envolvidos em tráfico e comércio ilegal no Brasil, as aves compreendem um dos grupos mais atingidos, especialmente devido a características como canto e colorido das penas. Atualmente, análises genéticas representam uma das formas mais eficazes de gerar dados para solucionar e minimizar os resultados de crimes ambientais e comércio ilegal de animais silvestres. Desta forma, este trabalho teve como objetivo realizar análises genéticas de sexagem em diversas aves, incluindo espécies comumente associadas ao tráfico de animais e apreendidas pela Polícia Ambiental e pelo IBAMA (Instituto Brasileiro do Meio Ambiente e dos Recursos Naturais Renováveis), e gerar um material de divulgação científica sobre tráfico e conservação deste grupo de vertebrados. Amostras de DNA foram obtidas de penas e sangue de 124 exemplares de 53 espécies das famílias Accipitridae, Cacatuidae, Cardinalidae, Cariamidae, Columbidae, Cuculidae, Emberezidae, Falconidae, Icteridae, Musophagidae, Psittacidae, Ramphastidae, Sturnidae, Thraupidae, Tinamidae, Trochilidae e Turdidae, mantidas junto a um Centro de Recepção, Triagem e Reabilitação de Animais Silvestres - CETAS (ONG Instituto Floravida, Botucatu, SP), a um Centro de Medicina e Pesquisa em Animais Silvestres - CEMPAS (Faculdade de Medicina Veterinária e Zootecnia, UNESP, Botucatu, SP) e a dois criadouros científicos de fauna silvestre para fins de conservação (Criadouro C.A., Itatiba, SP e Criadouro Poços de Caldas, Poços de Caldas, MG). Perfis genéticos sexo-específicos foram gerados por meio da amplificação de segmentos de DNA dos cromossomos Z e W. Um conjunto de primers que se anelam a regiões de éxons dos genes CHD-Z e CHD-W (chromo helicase-DNA binding) e que amplificam uma região de íntron que difere em tamanho entre os dois genes foi utilizado em PCR (Polymerase Chain Reaction) e os produtos de amplificação foram visualizados em gel de agarose 2%. ...
Keywords: Conservação biológica; Ave - Sexagem; Genetica animal; Genetica forense; Divulgação científica; Sexing